TEKNOLOGI INFORMASI SEBAGAI PEMODERASI PADA FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN - Widhiastuti, Ni Luh Putu; Sagung Oka Pradnyawati (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2023)
Financial reports are declared to have quality if they comply with the qualitative characteristics of financial reports, such as relevance, reliability, comparability and understandability. The purpose of this study was to examine the effect of education level, professionalism, leadership ethics, supervisory body functions on the quality of financial reports by using information technology as a moderating variable. This research was conducted at LPD Denpasar City. The method of determining the sample is non-probability sampling with saturated sampling technique so that 96 respondents are obtained. The analytical tool for testing hypotheses uses moderated linear regression (MRA) with the help of SPSS. The results showed that the level of education, professionalism and utilization of information technology had a positive effect on the quality of financial reports. On the other hand, leadership ethics and supervisory body functions do not affect the quality of financial reports. Utilization of information technology is able to moderate the relationship between education level and professionalism on the quality of financial reports. However, the use of information technology is not able to moderate the relationship between ethical leadership and the function of regulatory bodies on the quality of financial reports.